2010
DOI: 10.1016/s0924-9338(10)70722-7
|View full text |Cite
|
Sign up to set email alerts
|

P02-124 - The Need for Evaluation of Metabolic Parameters During Long Term Treatment with Clozapine

Abstract: Treatment with psychotropic drugs is frequently associated with obesity, dislipidemia, hyperglycaemia and hypertension, resulting in the development of the metabolic syndrome which in turn is an important risk factor for cardiovascular disease and type 2 diabetes mellitus. The atypical antipsychotics clozapine and olanzapine have the most pronounced effect on metabolic .parameters. Over the past years, several studies using the definitions of the so called Third Adult Treatment Panel (ATP-III) of the National … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Few studies have assessed the effects of the number of antipsychotics prescribed on metabolic parameters, 27 although several studies have compared metabolic parameters between patients who received antipsychotic monotherapy and those who received polypharmacy. 9 , 10 , 11 , 12 , 13 Our sample size ( n = 19,675) was substantially larger than that of previous studies ( n = 118–543), 9 , 10 , 11 , 12 , 13 which enabled the detection of a small yet statistically significant adverse effect of the number of antipsychotics prescribed on BMI and dBP using both univariate and multivariate analyses. The differences in BMI and dBP among the groups were small, and these parameters were within normal limits for all four groups.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Few studies have assessed the effects of the number of antipsychotics prescribed on metabolic parameters, 27 although several studies have compared metabolic parameters between patients who received antipsychotic monotherapy and those who received polypharmacy. 9 , 10 , 11 , 12 , 13 Our sample size ( n = 19,675) was substantially larger than that of previous studies ( n = 118–543), 9 , 10 , 11 , 12 , 13 which enabled the detection of a small yet statistically significant adverse effect of the number of antipsychotics prescribed on BMI and dBP using both univariate and multivariate analyses. The differences in BMI and dBP among the groups were small, and these parameters were within normal limits for all four groups.…”
Section: Discussionmentioning
confidence: 91%
“… 8 Although several cross‐sectional studies have examined the associations among antipsychotic polypharmacy and metabolic syndromes and metabolic parameters in patients with schizophrenia, findings are inconsistent, which may be attributed to the small sample sizes ( n = 118–543). 9 , 10 , 11 , 12 , 13 Using univariate analysis, Correll et al 10 found that patients treated with antipsychotic polypharmacy had higher rates of metabolic syndromes than those undergoing antipsychotic monotherapy. However, this result became non‐significant after controlling for relevant variables using multiple regression.…”
Section: Introductionmentioning
confidence: 99%
“…Antipsychotic polypharmacy was not a predictive factor for MetS in our study, which is similar to many studies (Misawa et al ., 2011; Steylen et al ., 2012; Aly El-Gabry et al ., 2018) but contrary to others (Heiskanen et al ., 2003; Cerit et al ., 2010). No statistically significant association was found between antipsychotic characteristics (number received, class of antipsychotic and route of administration) with the prevalence of MetS.…”
Section: Discussionmentioning
confidence: 99%